A re-evaluation of the cranial morphology and taxonomy of the Triassic dicynodont genus Kannemeyeria - Renaut, Alain, Joseph (University of the Witwatersrand, 2000)
The genus Kannemeyeria is one of the most important and distinctive taxa of the Triassic dicynodonts. It became the first Triassic dicynodont known to science, and thus forms the benchmark for the comparison of the evolution and morphology of other Triassic dicynodonts. An understanding of this genus forms an integral part of the biozonation of the Beaufort Group, and is pivotal in influencing the interpretation of the evolution, physiology and phylogenetic relationships of the Triassic dicynodonts. This study focuses on the detailed cranial morphology and relationships of the Kannemeyeria, and uses a rigorous morphological investigation as the basis for a meaningful elucidation of the functional and thus physiological aspects of this dicynodont. The descriptions demonstrate that variations related to the skull size, distortion or naturally occurring variation within the genus allow for the synonymy of the formerly recognised species K. latifrons Broom (1898; 1913), K. erithrea Haughton (1915) and K. wilsoni Broom (1937). This conclusion is further supported by the allometric analysis which cannot distinguish the variation observed in the holotypes with that occurring naturally within a growth series. Apart from the large specimen, the other smaller individuals are accommodated in the genus as different ontogenetic stages of the growth series represented by K. simocephalus Weithofer (1888). Several allometric variables show unusual patterns of development, indicating that Kannemeyeria can be subdivided into ontological classes, as juvenile and adult forms, separated from each other by a particular level of development. An age-related threshold level is suggested, and considered to represent an animal reaching sexual maturity. It is consequently proposed that the Kannemeyeria population was, at an age-related level, subdivided into sexually mature and immature groups but remained ecologically homogeneous. Both the descriptions and the allometric analysis of the species K. cristarhynchus Keyser & Cruickshank (1979) clearly indicate that it does not conform to the growth series of K. simocephalus and thus the differences observed between these two taxa are not constrained to size increases. Consequently, the recognition of the species K. cristarhynchus is considered valid. From the observations of the cranial morphology, tested using an allometric analysis, generic and specific diagnoses are constructed for Kannemeyeria and its two African species. Several features of Kannemeyeria are discussed in a functional context. A corrugated hom-covered snout and large caniniform processes are considered to be associated with defence and posturing behaviour. Several features of the braincase also suggest herding behaviour. Kannemeyeria also has a slightly different occipital musculature arrangement than that proposed for many other dicynodonts. Most Kannemeyeria cranial features are related to its masticatory function. From the analysis of masticatory cycle it is clear that the jaw action is described via a single pivot-point, which in Kannemeyeria approached the original, primitive position of the jaw hinge. The vertical orientation of the articulation and this pivot-point ensured that the muscle action during second phase of mastication produced an upward crushing and grinding action instead of the typical fore-and-aft motion of many other dicynodonts. It also meant that the muscle force was at their maximum, and little or no energy was lost to translation of the moment arm at the jaw articulation. Consequently, the Kannemeyeria masticatory cycle was both highly effective and extremely efficient. The morphology, and resultant physiology, of Kannemeyeria skull is considered to represent the innovative foundation for much of the success of many of the later Triassic dicynodonts.
Keywords: Paleontology -- Triassic; Reptiles; Fossil; Skull; Morphology